Pharmacological Approach to Smoking Cessation: An Updated Review for Daily Clinical Practice - Giulietti, Federico (High Blood Press Cardiovasc Prev, 2020)
Tobacco use is one of the major public health concerns and it is the most preventable cause of morbidity and mortality worldwide. Smoking cessation reduces subsequent cardiovascular events and mortality. Smoking is a real chronic disorder characterized by the development of an addiction status mainly due to nicotine. This condition makes the smokers generally unable to quit smoking without help. Different strategies are available to treat smoking dependence that include both non-pharmacological (behavioral counselling) and pharmacological therapies. Currently, it is well accepted that smoking cessation drugs are effective and safe in real-world settings. Nicotine replacement therapy (NRT), varenicline, bupropion and cytisine are the main pharmacological strategies available for smoking cessation. Their efficacy and safety have been proved even in patients with chronic cardiovascular disease. Each of these drugs has peculiar characteristics and the clinician should customize the smoking cessation strategy based on currently available scientific evidence and patient's preference, paying particular attention to those patients having specific cardiovascular and psychiatric comorbidities. The present document aims to summarize the current viable pharmacological strategies for smoking cessation, also discussing the controversial issue regarding the use of alternative tobacco products, in order to provide useful practical indications to all physicians, mainly to those involved in cardiovascular prevention.